Cyberbullying victimization, counterproductive work behaviours and emotional intelligence at workplace - Keskin, Halit; Akgun, Ali Ekber; Ayar, Hayat; Kayman, Saziye Serda (ELSEVIER SCIENCE BV, 2016)
As a new and inquiring concept, cyberbullying has attracted many researchers from a variety of disciplines. However, a specific context of the cyberbullying concept, workplace cyberbullying and its impact on employees' behaviors has rarely been theoretically reported in the literature. Addressing this particular gap in the literature, we develop a conceptual model encapsulating the relationship between workplace cyberbullying and counterproductive work behaviors (CWBs) and the role of employees' emotional intelligence on this relationship in particular. This study contributes to the literature in three ways. First, the theoretical framework proposed highlights the effects of workplace cyberbullying on employees' CWBs (i.e. CWB towards people (CWB-P) and CWB towards organization (CWB-O)). Hence the focus is, on distinguishing workplace cyberbullying from other cyberbullying types, and building a theoretical background for the relationship of workplace cyberbullying and CWBs variables. Second, based on Wong and Law's model this study aims to assess the possible role of emotional intelligence to eliminate undesirable behaviors at work. Thus we propose that having a high degree of emotional intelligence (EI) gives the employees the ability to handle workplace stressors better. Third, this research integrates organizational behavior literature to the emotional intelligence literature through offering a theoretical framework where employees' emotional intelligence is a process consisting of 1) others' emotion appraisal, 2) use of emotion, 3) self-emotion appraisal, and 4) regulation of emotion which allow them to deal with cyberbullying as a negative organizational behavior. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Cyberbullying; Workplace cyberbullying; Emotional intelligence; Counterproductive work behaviours; MEDIATING ROLE; ADOLESCENTS; STRESS; Business & Economics